THE EFFECT OF MOTIVATION ON SUSTAINABLE BUSINESS PERFORMANCE DEVELOPMENT AND THE MEDIATING RULE OF ENTREPRENEURIAL ORIENTATION AND SUSTAINABLE DEVELOPMENT IN CIPADU GARMENT SE's - TANGERANG - Arwini Sumardi (Business and Entrepreneurial Review, 2012)
Following motivation - entrepreneurial orientation - sustainable development - sustainable firm performance development, this paper aims to explore how the first three variables support sustainable firm performance development of SEs in Banten province. Fieldwork was performed in Cipadu Business District-Tangerang, Banten province. A survey of 238 SEs provided data for empirical testing with SEM analysis. The findings suggested that the first three variables influence the SEs s sustainable firm performance development in a positive way Significantly. The owners of SEs pay more attention to improve motivation, entrepreneurial orientation, and sustainable development, to gain sustainable firm performance development. The sequential of the four variables above play roles as the tools on increasing SEs profit and revenue. Motivation variable and entrepreneurial orientation especially is the power engine for getting SEs performance. Sustainable development implication changes the paradigm of SEs future life as smart businesses, for gaining SEs profit and revenue. Quantitative evaluation of the effects of motivation, entrepreneurial orientation embedded concept of sustainable development (triple bottom line) in the Cipadu garment business in an important research gap.